Maine Forests: A Century of Change, 1900-2000…and elements of policy change for a new century - Irland, Lloyd (Maine Policy Review, 2000)
At the close of the 19th century, the state’s forest area was at an all time low; land ownership was changing rapidly with the emergence of new paper companies; a growing number of wildlife species were threatened; and widespread unease over the future of Maine’s forests was evident. Today a similar unease is evident. Many believe the state’s spruce-fir forest is being overcut; land ownership is changing rapidly; fear exists that the sustainability of Maine’s forests; and wildlife populations have been severely compromised. Given the similarity in circumstance, one might ask whether there has been any change over the past century. To help us reflect on where we’ve been, where we are today, and how we might proceed in the future, Lloyd Irland presents seven different images of Maine’s forest. Each corresponds to a value of the forest; some correspond to policy agendas. Irland argues that the pragmatic approach to managing Maine’s forest for the future includes all of these values and does not place a greater importance on one to the exclusion of others. Further, he notes that cooperative approaches that advocate incremental change show the greatest promise for achieving real results.
Keywords: Maine North Woods; Maine forests; forest management